Forecasting longevity for financial applications: A first experiment with deep learning methods - Bravo, Jorge M. (2023)
Bravo J.M. (2021) Forecasting Longevity for Financial Applications: A First Experiment with Deep Learning Methods. In: Kamp M. et al. (eds) Machine Learning and Principles and Practice of Knowledge Discovery in Databases. ECML PKDD 2021. Communications in Computer and Information Science, vol 1525. Springer, Cham. https://doi.org/10.1007/978-3-030-93733-1_17